Effectiveness Model of Coastal Forest in Pananjung Nature Reserve, Pangandaran as Tsunami Buffer - Denni Susanto; Lies Rahayu Wijayanti Faida; Sunarto Sunarto (Jurnal Ilmu Kehutanan)
The southern coast of Java is a coastal area prone to tsunami. In 2006, a tsunami with a magnitude of 6 Richter scale happened in Pangandaran area including Pananjung Nature Reserve. The presence of coastal forest in the Pananjung Nature Reserve reduced the force of the tsunami so that the destructive effect of the tsunami can be minimized. This research aimed to model and assess the effectiveness of coastal forest in Pananjung Nature Reserve as a tsunami buffer. Nested sampling was used to collect vegetation data with 4% sampling intensity. Extensive coastal forest of 38 ha was measured in 38 square forest sample plots with the size of the plot for the understorey 1 mx 1 m, seedlings 2 m x 2 m, saplings 5 mx 5 m, poles 10 m x 10 m, and trees 20 x 20 m. The plots were located purposively by considering the location of tsunami inundation and vegetation density. The vegetation density was performed by image analysis of Sentinel 2-A2017. The effectiveness of coastal forests as tsunami buffers was analyzed using mathematical concepts according to Harada and Imamura (2003) and modeled with Spatial Multi Criteria Analysis (SMCA) with width coastal vegetation criteria, vegetation density, tree diameter, and density of understorey. The results showed that in Pananjung Nature Reserve has vegetation density > 2000 ind/ha, average tree diameter of 15.94 cm, and coastal forest width between 120 m - 325 m. Topography of coastal forest Pananjung Nature Reserve waved between 0 m asl - 59 m asl. It was found that the effectiveness of coastal forest Pananjung Nature Reserve in reducing energy tsunami was in the value of 41.18%, thus it was included in the effective category.